INTEGRATED PUBLIC SPACE DESIGN WITH A PASSIVE ARCHITECTURAL APPROACH IN THE TINGKIR SUB-DISTRICT, SALATIGA - Maqbul Kamaruddin; Widi Dwi Satria; Dewanto Harjunowibowo; Nofri Sumedi Jaya; Fernando Raja Monang; Yohanes Glen Owen (Jurusan Arsitektur, 2023)
Public places that provide a secure, welcoming, and beautiful environment are becoming increasingly important to enhance community welfare. The government is attempting to enhance public services in Salatiga's Tingkir sub-district by creating an integrated public space design for the neighbourhood. Presenting this integrated public space is difficult as it must allow for various community activities in a typical community area, including sports, education, recreation, and events. In response to this problem, a passive design strategy that optimises building operations and conserves resources by considering context and microclimate elements is given in the design of a public space. These include modifications to the traditional Javanese stilt house form, skylights for daylighting, and roof protection against predicted excessive rains and sunshine. Integrated public space planning aims to fulfil many communities' requirements and provide a visually stunning and sustainable environment for everyone via these strategies. This study's most effective passive design techniques are adapting the traditional stilt house model to increase natural ventilation on artificial cooling systems and roof protection as shading, which can effectively regulate temperature. These methods are anticipated to enhance public spaces' overall sustainability and livability, transforming them into ecologically conscious and neighbourhood-focused hubs of activity and engagement.